Cognitive performance in midlife type 2 diabetes: results from the ENBIND study. Issue 6 (13th October 2020) - Dyer, A. H.; McKenna, L.; Gamage, G.; Bourke, N. M.; Killane, I.; Widdowson, M.; Woods, C. P.; Gibney, J.; Reilly, R.; O'Neill, D.; Kennelly, S. P.
Abstract: Aims: To establish the impact of uncomplicated type 2 diabetes on cognitive and neuropsychological performance in midlife. Methods: We performed a cross‐sectional study of middle‐aged adults with uncomplicated type 2 diabetes and a cohort of healthy control participants. General cognition was assessed using the Montreal Cognitive Assessment test and neuropsychological assessment was undertaken using a detailed neuropsychological assessment battery. Results: A total of 152 participants (102 with type 2 diabetes and 50 controls) were recruited (mean age 52 ± 8 years, 51% women). Participants with midlife type 2 diabetes were more than twice as likely to make an error on the Montreal Cognitive Assessment test [incidence rate ratio 2.44 (95% CI 1.54 to 3.87); P  < 0.001]. Further, type 2 diabetes was also associated with significantly lower memory composite score [β: −0.20 (95% CI −0.39 to −0.01); P  = 0.04] and paired associates learning score [β: = −1.97 (95% CI −3.51, −0.43); P  = 0.01] on the neuropsychological assessment battery following adjustment for age, sex, BMI, educational attainment and hypercholesterolaemia. Conclusions: Even in midlife, type 2 diabetes was associated with small but statistically significant cognitive decrements. These statistically significant decrements, whilst not clinically significant in terms of objective cognitive impairment, may have important implications in selecting out individuals most at risk of later cognitive decline for potential preventative interventions in midlife.